Modelling- and Simulation-Based Design of Multi-tier Systems - Zellag, Kamal; Vangheluwe, Hans (Electronic Communications of the EASST, 2012)
This paper introduces a domain-specific language for modelling andsimulation-based design of multi-tier systems. Multi-tier systems are complexand very few general models have been developed. Rather, models are alwaysdedicated to a specific architecture. Our approach allows for rapidexperimentation with different multi-tier alternatives. Not only parameters,but also structure can be drastically varied. Using graph transformation,multi-tier systems models are translated into Queueing Petri Nets (QPNs) in asystematic way for analysis with the SimQPN simulator. We describe QPN, ourmulti-tier architecture visual language, as well as the transformation between them. A case study demonstrates the power of the approach for design-space exploration.